2020
DOI: 10.3389/fmicb.2019.03135
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium Inoculation Drives the Shifting of Rhizosphere Fungal Community in a Host Genotype Dependent Manner

Abstract: Rhizosphere microorganisms play important roles in plant health and nutrition, and interactions among plants and microorganisms are important for establishment of root microbiomes. As yet, plant-microbe and microbe-microbe interactions in the rhizosphere remain largely mysterious. In this study, rhizosphere fungal community structure was first studied in a field experiment with two soybean cultivars contrasting in nodulation grown in two rhizobium inoculation treatments. Following this, recombinant inbred line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…Organic carbon and nitrogen produced by the photosynthesis-nitrogen fixation machinery of legumes and rhizobia supports consumers at various trophic levels. Consumers are affected by compatible relationships between host plants and Rhizobium species (Dean et al, 2014;Naluyange et al, 2014Naluyange et al, , 2016Pulido et al, 2019;Karoney et al, 2020;Xu et al, 2020). Consumers are also affected by antagonisms arising from incompatible relationship between host plants and rhizobium species (Gourion et al, 2015;Clúa et al, 2018; Modi et al, 1985;Guerinot et al, 1990;Deshwal et al, 2003a Rhizobium Rioux et al, 1986;Dilworth et al, 1998;Deshwal et al, 2003a Benezech et al, 2020a).…”
Section: Phytochemicals In Rhizobium-legume Symbiosis and Their Influmentioning
confidence: 99%
“…Organic carbon and nitrogen produced by the photosynthesis-nitrogen fixation machinery of legumes and rhizobia supports consumers at various trophic levels. Consumers are affected by compatible relationships between host plants and Rhizobium species (Dean et al, 2014;Naluyange et al, 2014Naluyange et al, , 2016Pulido et al, 2019;Karoney et al, 2020;Xu et al, 2020). Consumers are also affected by antagonisms arising from incompatible relationship between host plants and rhizobium species (Gourion et al, 2015;Clúa et al, 2018; Modi et al, 1985;Guerinot et al, 1990;Deshwal et al, 2003a Rhizobium Rioux et al, 1986;Dilworth et al, 1998;Deshwal et al, 2003a Benezech et al, 2020a).…”
Section: Phytochemicals In Rhizobium-legume Symbiosis and Their Influmentioning
confidence: 99%
“…Although many studies have demonstrated that PGPR play a key role in affecting the biological characteristics of plants through changes in composition and structure of rhizobiome, most of the studies have focused on only one time point and one influencing factors, and the regulation of rhizomicrobiome by a certain microorganism in the entire life cycle of plant growth has been rarely studied 7 . Currently, non-cultivation methods with high-throughput sequencing technology have been widely applied in studies on rhizomicrobiome that overcome the limits of microbial culture and isolation technology.…”
Section: Introductionmentioning
confidence: 99%
“…In rhizosphere, the bacteria so called plant growth promoting rhizobacteria (PGPR) 5 could promote plant growth by various mechanisms, such as inhibiting phytopathogens, improving plant nutrient supply, producing phytohormones, and modifying physicochemical properties of soil 6 . On the other hand, PGPR also can affect the composition of microbial communities in the rhizosphere (rhizomicrobiome) of associated plants, which in turn affect the health of the entire soil microbiome 7,8 and affect the growth of plants. Zhang et al 9 identified a consortium of three PGPR strains (Bacillus cereus AR156, Bacillus subtilis SM21, and Serratia sp.…”
mentioning
confidence: 99%
“…The microbiota of vegetables includes fungi, protozoa and bacteria that can negatively influence their crop production. Beneficial relationships can also happen, such as the symbiosis of several species of microorganisms in the root of leguminous plants (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%